Development of Android-Based Learning Media Assisted by Appypie Pythagorean Theorem Material - Nurhayati, Siti; Hakim, Dori Lukman (Sahabat Publikasi, 2024)
Along with the influence of smartphones in terms of information and communication in every daily activity for both students and teachers, this causes the concentration and learning time of students to decrease. Based on the needs analysis interview results, information was obtained that students liked the material presented in the form of an Android application. This study aims to determine the feasibility of developing an Android-based learning media assisted by Appypie for the Pythagorean theorem material and student responses. The research method for developing Android-based learning media uses the R&D (Research and Development) development method. The development model used in this study refers to the 4-D development model from Thiagarajan, which consists of (1) Define, (2) Design, (3) Develop, and Disseminate. Data collection techniques in this study were interviews and questionnaires. Research instrument validation sheet of experts and students. The results of the research on the development of Android-based learning media assisted by Appypie are